Idārah Ta - Mir'atun Hasanah; Ade Destri Deviana (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2020)
Rasyidiyah Khalidiyah Islamic Boarding School is an Islamic boarding school in South Kalimantan. It is famous for Kitab Kuning (The Classical Books) and it focuses on function of language as system, which means that Arabic is an instrument to understand the classical books/kitab kuning. This Islamic boarding school has been synchronized with Public Islamic High School standard today. The purpose of this study is to know the planning, organizing, directing, coordinating, and monitoring of learning Arabic language based on Sears